Transient desires [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2021)
"Two young America women are badly injured in a boating accident while joy riding in the Laguna with two young Italians. However, Guido Brunetti's curiosity is aroused by the behavior of the young men, who abandoned the victims after taking them to the hospital. As Brunetti and his colleague, Claudia Griffoni, investigate the incident, they discover that one of the young men works for a man rumored to be involved in more sinister nighttime activities in the Laguna. Brunetti needs to enlist the help of unfamiliar colleagues to solve a peculiarly horrible crime whose ruthlessly organized perpetrators are technologically brilliant."--Back cover.